Achieving Supply Chain Resilience: the role of procurement. Issue 5 (21st August 2014) - Pereira, Carla Roberta; Christopher, Martin; Da Silva, Andrea Lago
Abstract : Purpose: Achieving resilience along the supply chain in today's turbulent business environment requires efforts from both internal and external elements of the extended enterprise. The purpose of this paper is therefore to understand the role of procurement in identifying and managing the intra- and inter-organisational issues which impact supply chain resilience. Design/methodology/approach: The systematic literature review was conducted between 2000-2013 with the objective being to answer the single research question proposed. To do so, a content analysis based on the literature was applied to 30 selected papers. Findings: The study revealed that procurement activities do make a significant contribution to creating supply chain resilience. Emerging from the literature review, certain intra- and inter-organisational issues were identified that could impact supply chain resilience. Also the possible actions that procurement could take to enable the enhancement of supply chain resilience were identified. Research limitations/implications: This study is limited in that it is exploratory and focuses only on the body of knowledge presented in two databases over the past 13 years. It has also been restricted to the procurement function and the consequent implications for the upstream supply chain. Originality/value: The originality of this paper lies in the identification of intra- and inter-organisational issues from a procurement perspective specifically as they relate to improving supply chain resilience. This raises further questions on the role of procurement in creating supply chain resilience, which has not been well-explored in the current literature.